Behavioural study of completely overlapped tubular joints under monotonic and cyclic axial loading - Yang, Ye (2008)
In the current study, the structural behaviour of the completely overlapped tubular joint under monotonic and cyclic loading is experimentally and numerically investigated. Two completely overlapped tubular joint specimens are tested to failure under monotonic and quasi-static cyclic loading. A total of 3888 FE models of the completely overlapped tubular joints are created with various geometrical parameters to investigate the effect of geometrical parameters. The failure mechanism and the ultimate strength of the joint are the two main areas of study. The failure modes of the joint under lap brace axial compression include the through brace wall plastification, the lap brace yielding, the lap brace local buckling and the lap brace member failure. A combination of these failure modes can be occurred depending on the geometrical parameters of the joint. A set of parametric equations is proposed for predicting the ultimate capacity of the completely overlapped tubular joint under lap brace axial compression. The reliability of the proposed equations has been verified against the current FE models and the test data. A simplified characteristic strength equation is also proposed for design of tubular joints with complete overlap of braces. Apart from the ultimate capacity under static loading, the effect of geometrical parameters and load characteristics on the cyclic behaviour of completely overlapped tubular joints is also investigated. It is recommended that the dissipative zone of the completely overlapped tubular joint under cyclic loading should be designed at the short segment of the through brace joining the chord.